The Effect of Support Group Therapy on Bullying Victim’s Resiliency in An Islamic Boarding School Setting - Rizka Yunita; Widya Addiarto (Babali Nursing Research, 2023)
Introduction: Bullying becomes a subset of intentional aggressive behavior that occurs globally. It allows the invasion of negative experiences, triggering feelings of discouragement, hopelessness, desperation, and insecurity, leaving the victims in powerless and indefensible circumstances toward the vicious bullying attacks. Thus here, we ought to investigate the influence of support group therapy on resilience among bullying victims in an Islamic boarding school setting. Method: This was a quasi-experimental study with a pre-posttest design with the control group. A total of 64 eligible participants that selected by the purposive sampling technique then equally distributed into the experimental and control groups. This research was conducted from May to June 2023 at Islamic Boarding School. Data were collected using the Resilience Scale Questionnaire which consists of 25 question items with answer choices using a Likert scale. Result: The results showed that the difference in resilience before and after the intervention in the control group showed a p value of 0.080, while in the treatment group the difference in resilience showed a p value of 0.000 before and after the intervention. The difference in the resilience scores of the control and treatment by the Wilcoxon test showed the p-value of 0.000, these results show that the significant effect of support group therapy on bullying victims’ resiliency. Conclusion: Support group therapy conclusively concentrates on providing adequate support and reinforcement to the bullying victims, cultivating empathy to restore their confidence and resiliency. Furthermore, this therapy can be implemented in mental health and community nursing settings as an alternative therapy. Keywords: Bullying, Resilience, Support Group Therapy